Functions of the indian mutual fund industry - R, Saravanaselvi; K, Thiruppathy (Journal of Management and Science, 2013)
Investment is a commitment of funds in real assets or financial assets. Investment involves risk and gain. In the present dynamic global environment, e x p l o r i n g investment a v e n u e s a r e of g r e a t r e l e v a n c e .Investment skills developed over a period of time are considerably influenced by experience and spadework carried out to arrive at conclusions. The success of an investment acti vit y depends on the knowledge and ability of investors to invest, the right amount, in the right type of investment, at the right time. Real assets, being tangible material things, are less liquid than financial asset Compared to financial assets, returns on real assets are more difficult to measure accurately due to the absence of broad, ready, and active market. Financial assets available to individual investors are manifold, having different concomitant benefits to choose from. All financial investments are risky but the degree of risk and return differ from each other. An investor has to use his discretion, which is an art acquired by l earning a n d pra ct i cal experience. The knowledge of financial investment and the art of its management are the basic requirements for a successful investor Financial system comprises of financial institutions, services, markets and instruments,which are closely related and work in conjunction with each other. The litany of new financial institutions and instruments developed in recent years, with the ostensible objective of modernizing the financial sector, is impressively long; Mutual Funds, Discount and Finance House of India, Money Market Mutual Funds, Certificate of Deposit, Commercial Paper, Factoring and Treasury Bills. Financial services through the network of elements serve the needsofindividuals, institutionsand companies. It is through these elements, the functioning of the financial system is facilitated. Over the years, the financial services in India have undergone revolutionary changes and had become more sophisticated, in response to the varied needs of the economy. The process of financial sector reforms, economic liberalization and globalization of Indian Ca pi tal Market had generated and augmented the interest of the investors in equity. But, due to Inadequate knowledge of the capital market and lack of professional expertise, the common investors are still hesitant to invest their hard earned money in the corporate securities. The advent of mutual funds has helped in garnering the investible funds of this category of investors in a significant way.